See and Spy Shapes Baby Einstein - Julie Aigner (Mexico Hyperion Book, 2001)
Shapes invites babies and young children to identify different shapes in bold, graphic illustrations featuring the Baby Einstein characters. Playful poems will inspire children to seek out shapes in the world around them.